THE MEDIATING EFFECT OF SATISFACTION ON STUDENT LOYALTY TO HIGHER EDUCATION INSTITUTION - Kunanusorn, Anusorn; Puttawong, Duangporn (European Scientific Journal, ESJ, 2015)
Main purposes of this study were to examine links between student perceived value, student trust, university image, and student satisfaction to student loyalty and to describing an influence relationship of mediator variables in student loyalty model. The model was tested through the use of Partial Least Squares (PLS) structural equations methodology. Empirical data were drawn from 100 private university students in the upper north of Thailand. Questionnaire method and multi - stage sampling techniques were used in collecting data with an error 1% sample size. Data analysis with descriptive statistics and structural equations model analysis were used to test hypothesis model. Results from this study indicated that the student satisfaction (SATIS) and three antecedent variables: university image (IMAGE), student trust (TRUST), and student perceived value (PERC) have positive influence to student loyalty (STULOY) with statistical significant level 0.05. This model was perfectly fit with an empirical data and was predicted by student satisfaction and antecedent variables up to 82.5%. Moreover, the results also show that student perceived value was the construct that most influence to university image and student trust, and strongly indirect influence to student satisfaction. The influence of perceived value is also relevant to student loyalty via student satisfaction. The most important issue is an impact of student satisfaction variable that has highest directly influence and transmits relative influence linkage between antecedent variables and dependent variable. In conclusion, student satisfaction was a mediating variable and it implied that the student satisfaction was the major driver of student loyalty.